Black Social Workers Matter: Using Parallel Narratives to Discuss Social Work History. (2nd January 2023) - Parker, Amittia
ABSTRACT: This article presents parallel narratives as a pedagogical strategy to increase awareness, facilitate critical reflection, and dialog about the role of Black social work pioneers in the development of the social work profession. Using this approach, history is reconstructed and presented in ways that decenter Whiteness and avoid marginalizing people of color. The Black settlement house movement that occurred simultaneous with Jane Addams's Hull House, the work of Lugenia Burns Hope alongside Mary Richmond, and the work of W. E. B. Du Bois and Bertha Reynolds, are parallel narratives discussed. This article intentionally shares the history of the social work profession with multiple narratives, and in addition emphasizes that doing so is a step toward the realization that Black Social Workers Matter.